Hubungan Antara Religiusitas dengan Penyesuaian diri Pada Santri Baru Pondok Pesantren Darul Hikmah Kisaran - Husri Marliani Mawaddah Sihombing; Suryani Hardjo (Jouska: Jurnal Ilmiah Psikologi, 2022)
The purpose of this study was to determine the relationship between self-adjustment and religiosity in the new students of Darul Hikmah Kisaran Islamic Boarding School. The hypothesis proposed that there is a positive relationship between adjustment and religiosity in new students. The population is new students at the Darul Hikmah Kisaran Islamic Boarding School which opened 73 people with total sampling technique. The data collection method used two scales, namely the adjustment scale and religious scale. The data analysis method used in this research is the product moment correlation technique from Karl Pearson. The results showed that there was a positive and significant relationship between self-adjustment and religiosity seen from the coefficient value (Rxy) = 0.483 with p = 0.000 0.050. The value of the effective contribution given is 23.4%. This means that the higher the religiosity of the Darul Hikmah Kisaran Islamic Boarding School students, the higher their adjustment. On the other hand, increasing the low religiosity of the Darul Hikmah Kisaran Islamic Boarding School students makes their adjustment lower. So it can be said that there is a significant relationship between adjusting to religiosity in the new students of the Darul Hikmah Kisaran Islamic Boarding School. The empirical average value of self-adjustment = 119.67 while the hypothetical average value = 92.5 so that the self-adjustment variable is high, as well as the empirical mean value of religiosity = 120.32 while the hypothetical average value is = 95 so that the religiosity variable is high.The purpose of this study was to determine the relationship between self-adjustment and religiosity in the new students of Darul Hikmah Kisaran Islamic Boarding School. The hypothesis proposed that there is a positive relationship between adjustment and religiosity in new students. The population is new students at the Darul Hikmah Kisaran Islamic Boarding School which opened 73 people with total sampling technique. The data collection method used two scales, namely the adjustment scale and religious scale. The data analysis method used in this research is the product moment correlation technique from Karl Pearson. The results showed that there was a positive and significant relationship between self-adjustment and religiosity seen from the coefficient value (Rxy) = 0.483 with p = 0.000 0.050. The value of the effective contribution given is 23.4%. This means that the higher the religiosity of the Darul Hikmah Kisaran Islamic Boarding School students, the higher their adjustment. On the other hand, increasing the low religiosity of the Darul Hikmah Kisaran Islamic Boarding School students makes their adjustment lower. So it can be said that there is a significant relationship between adjusting to religiosity in the new students of the Darul Hikmah Kisaran Islamic Boarding School. The empirical average value of self-adjustment = 119.67 while the hypothetical average value = 92.5 so that the self-adjustment variable is high, as well as the empirical mean value of religiosity = 120.32 while the hypothetical average value is = 95 so that the religiosity variable is high.